A strain energy based multiaxial high-cycle fatigue life evaluation model for notched structures - Gezer, Burak. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
In this study, a model is presented for high-cycle fatigue-life assessment of notched engineering components subjected to constant amplitude multiaxial proportional loads. The algorithm requires only material-dependent parameters available in material data sheets. Applicability of the proposed approach is independent of any experimentally determined factor for geometry as well as loading conditions. Instead, the effects of such factors are taken into consideration in this study through a newly introduced parameter called equivalent strain energy density. The formalized fatigue design methodology estimates the fatigue life by directly using elastic stress and strain fields around the notch in conjunction with Coffin Manson-Basquin law. Stress/strain states developed in the part are determined via linear elastic finite element analysis. Predictions of the presented model are compared with many experimental results reported in the literature for specimens with various notch geometries made of different materials, including aluminium alloys and steels, subjected to different types of multi-axial loads and a remarkable level of accuracy is reached.
Keywords: Buildings.